Harnessing the Power of the Electronic Medical Record to Facilitate an Opt-Out HIV Screening Program in an Urban Academic Emergency Department. Issue 3 (May 2017) - Lin, Janet; Mauntel-Medici, Cammeo; Heinert, Sara; Baghikar, Sara
Abstract : Emergency Departments (EDs) are important settings for routine HIV screening because they are safety nets for populations with limited access to primary care and high risk for HIV infection. However, EDs rarely perform routine HIV screening due to logistical barriers. An electronic medical record (EMR)-driven routine opt-out HIV screening program was implemented in an urban academic ED and led to rapid scale-up of screening volume and detection of unknown HIV infection. The streamlined tool, requiring 4 mouse clicks, automates screening for eligibility, facilitates documentation of consent and orders the HIV test. HIV screening increased to a monthly average of 550 tests compared to an average of 7 tests prior to program implementation. Similar EMR innovations can be leveraged in a variety of other clinical settings and for testing of other diseases to improve clinical flow and outcomes. Abstract : Supplemental Digital Content is Available in the Text.